Measuring Congregational Functioning: A Scale Based Upon Bowen Family Systems Theory - Stewart-Sicking, Joseph A. (Pastoral psychology, 2026)
Valid, systems-level measurements of congregational health are few in the literature. To meet this need, this study created a measure based upon Bowen family systems theory, which is often used by congregational leaders but heretofore lacks empirical validation. Items were constructed based upon Papero et al.’s (Systems, 6(2), Article 19, 2018) systems model for family assessment (SMFA) and reviewed by experts to create a pool representative of SMFA constructs. To evaluate the reliability and structure of the instrument, a sample of 350 congregational leaders, primarily American Christians from across denominational lines, completed the items through an online survey. This sample was randomly split into equal halves for two stages of data analysis. In stage 1, exploratory factor analysis indicated a single underlying construct. Items were selected for their difficulty, discrimination, and content validity concerns to create a 10-item scale with a reliability of α = .908. In stage 2, the scale’s validity was α = .910 and a confirmatory factor analysis showed that a single factor was a good fit for the data (RMSEA = .03). Additionally, the composite score correlated with congregational coping with the COVID-19 crisis. The functioning of congregations was found to be both consistent with the SMFA and reliably measurable.